Tingkat Pengetahuan dengan Perilaku Personal Hygiene Remaja Putri Pada Saat Menstruasi di Desa Tuntungan II - Nurhayati, Nurhayati; Putri, Adelia; Raihan, Ahmad Fitra; Maulana, Alfian; Siregar, Anisa Putri; Darmayanti, Darmayanti; Yulianti, Dena; Panggabean, Hikmah Tin; Rifda, Khairun Rani Mawa; Purba, Khairunnisa Insani; Zahra, Klisa Putri; Harahap, Muhammad Irwandi; Tanjung, Putri Keza Hidayah; Batubara, Rini Warahmah; Masyithah, Ruhul; Salsabila, Salsabila; Ritonga, Sela; Siregar, Siti Romaito; Ramadan S, Suci Aulia (Health Information : Jurnal Penelitian, 2023)
This study aims to evaluate the level of knowledge and personal hygiene behavior of adolescent girls during menstruation in Tuntungan II Village, Pancur Batu District, Deli Serdang Regency, North Sumatra. Through a quantitative approach with a cross-sectional research design, data was collected from 30 young women via questionnaire on November 11 2023. The results showed that the majority of respondents had a good (53.3%) and sufficient (40%) level of knowledge about personal hygiene. during menstruation, with only 6.7% having a poor level of knowledge. In terms of personal hygiene behavior, the majority of respondents showed good behavior (83.3%), while 13.4% rated their behavior as adequate, and only 3.3% had poor behavior. Based on these findings, it is recommended to increase personal hygiene education, especially regarding menstruation, both through formal education in schools and through outreach campaigns in the community. It is necessary to provide more comprehensive material and increase the accessibility of information through the use of the internet and digital resources. Apart from that, supporting families in an active role in providing education to young women through seminars or family discussion groups can also help build a shared understanding of the importance of personal hygiene during menstruation. It is hoped that these steps can improve the reproductive health of young women in Tuntungan II Village and its surroundings.